Cell cycle checkpoint revolution: targeted therapies in the fight against malignant tumors - Song, Guangming; Liu, Jue; Tang, Xing; Zhong, Jie; Zeng, Yuhuan; Zhang, Xiaodi; Zhou, Jianbin; Zhou, Jie; Cao, Lu; Zhang, Qunfeng; Li, Yukun (Frontiers in Pharmacology, 2024)
Malignant tumors are among the most important causes of death worldwide. The pathogenesis of malignant tumors is complex and has not been fully elucidated. Studies have shown that the pathogenesis of malignant tumors is related to abnormal cell cycle progression. The expression levels of cyclins, cyclin-dependent kinases (CDKs) and CDK inhibitors and the function of cell cycle checkpoints determine whether the cell cycle can proceed smoothly. Cell cycle-targeting drugs have the advantages of specificity, low toxicity and side effects, and reduced drug resistance. Identifying drugs that target the cell cycle and applying them in clinical treatment will promote the development of chemotherapy for malignant tumors. This article aims to review the targeted drugs against the cell cycle and their mechanism of action.